Nuclear coherent versus incoherent effects in peripheral RHI collisions - Bracco, M. E. [UNESP]; Nemes, M. C. (Elsevier, 1995)
We derive simple and physically transparent expressions for the contribution of the strong interaction to one-nucleon-removal processes in peripheral relativistic heavy-ion collisions. The coherent contribution, i.e., the excitation of a giant dipole resonance via meson exchange, is shown to be negligible as well as the interference between Coulomb and nuclear excitation. The incoherent nucleon-knockout contribution is also derived suggesting the nature of the nuclear interaction in this class of processes. We also justify the simple formulae used to fit the data of the E814 Collaboration. © 1995 Elseier Science B.V. All rights reserved.